2015
DOI: 10.4103/0970-9185.155221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Macintosh laryngoscope and C-MAC video laryngoscope for intubation in lateral position

Abstract: Background and Aims:Endotracheal intubation is conventionally performed when the patient is in supine position. It may be required to secure airway in laterally positioned patient. Tracheal intubation in lateral position seems to be difficult because the laryngeal view is compromised. Hence, C-MAC video laryngoscope (Karl Storz, Germany), a newer device using a modified macintosh blade may be useful for intubation in lateral position.Material and Methods:A total of 100 American Society of Anesthesiologists Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Hence, we compared the hemodynamic response to oral endotracheal intubation using McCoy and C-MAC laryngoscopy with that of conventional Macintosh laryngoscopy in adult patients posted for elective surgery under general anesthesia. One recent study[6] has shown that C-MAC ® videolaryngoscopy needed less duration of laryngoscopy for successful intubation compared to Macintosh laryngoscopy even in lateral position. Duration of laryngoscopy is an expected variable to affect the degree of hemodynamic response to endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we compared the hemodynamic response to oral endotracheal intubation using McCoy and C-MAC laryngoscopy with that of conventional Macintosh laryngoscopy in adult patients posted for elective surgery under general anesthesia. One recent study[6] has shown that C-MAC ® videolaryngoscopy needed less duration of laryngoscopy for successful intubation compared to Macintosh laryngoscopy even in lateral position. Duration of laryngoscopy is an expected variable to affect the degree of hemodynamic response to endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…So, time to best laryngeal view and intubation attempts may be increased with DL compared with video laryngoscope, which offers a magnified, brighter image with a quick insertion in the pharyngeal midline without displacing the tongue. [ 11 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Th e simplicity of glottic visualization is not always followed by easy tube insertion and longer intubation time may be required [1][2][3]8,19 . In the study by Bhat et al 20 , signifi cantly shorter intubation time was recorded in video group, although intubation was performed in diffi cult lateral position. Unlike these results, our study showed nonsignifi cant diff erence in intubation time, and there were no diffi culties in tube insertion despite using different stylets in study groups.…”
Section: Discussionmentioning
confidence: 99%